การเปิดเผยตัวตน บรรยากาศที่สนับสนุนในสถานที่ทํางาน และการถูกเลือกปฏิบัติในสถานที่ทํางาน ในกลุ่มผู้ชายข้ามเพศ - สุชานรี ศรีวิลัย (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
Transgender men are assigned female at birth but identify with a gender different from their assigned sex. This research aimed to examine the relationship between a supportive workplace climate and discrimination in the workplace moderated by, disclosure. The study also explored levels of disclosure and discrimination among transgender men with different gender identities and sexual orientations. Data were collected from 128 transgender men working in organizations based in Thailand through an online survey. The research findings were as follows: (1) A supportive workplace climate was negatively related to workplace discrimination (β = - .719, p < .001). (2) Regarding the moderating effect, implicit outness of disclosure did not moderate the relationship between a supportive workplace climate and discrimination (β = .067, p = .268). Similarly, explicit outness of disclosure did not moderate the relationship (β = -.010, p = .858). (3) The findings showed no significant differences in disclosure among transgender men across gender identity groups (F = 0.52, p = 0.96) or sexual orientation groups (F = 0.92, p = 0.57). However, transgender men with diverse gender identities experienced more direct (t = -2.98, p < .001) and indirect discrimination (t = - 3.37, p < .001), compared to those with binary gender identities. Similarly, transgender men with diverse sexual orientations experienced greater direct (t = - 2.06, p = .041) and indirect discrimination (t = - 2.15, p = .033) in the workplace, compared to those with heterosexual orientations. This research provided insights for organizations to design supportive workplace climate that reduces workplace discrimination. Though the moderating effect was not found, organizations can still apply these findings to acknowledge and support transgender men in Thai workplaces by fostering an inclusive culture and implementing diversity-friendly policies.